An Insight into Novel Sperm Cell Proteins as Bio-markers for Male Infertility: A Review - Kumar, Naina; Singh, Namit K. (Current Molecular Medicine, 2021)
Male infertility is rising nowadays and accounts for a major part of infertility cases worldwide. Novel tests are being developed for better detection and management of male infertility. Though there are many tests available for diagnosing male infertility like acrosome reaction rate, hemizona assay, in vivo or in vitro sperm penetration assay, sperm DNA damage tests, however, a semen analysis is the most commonly used initial test for male infertility. It is usually associated with failure to detect the cause in many cases, as seminal composition gets affected by a number of factors and can give false reports. Furthermore, it does not give any information about defects in capacitation, sperm-zona pellucida interaction, and sperm’s ability to fertilize oocytes. This results in failure of detection and delayed management of male infertility. Hence, the present review was conducted to identify various sperm proteins that play a significant role in spermatogenesis, sperm motility, sperm-zona pellucida interaction, and fertilization. These proteins can be used in the future as markers of male infertility and will aid in better detection and management of male infertility. Methodology: Search for literature was made from 1970 to 2020 from various databases like PUBMED, SCOPUS, Google Scholar on sperm proteins and their role in male fertility using keywords: “sperm protein as bio-markers”, “novel sperm proteins as markers of infertility”, “Sperm proteins essential for capacitation, sperm motility and oocyte fertilization”. Inclusion criteria: All full-length research articles, systematic reviews, meta-analyses, or abstracts on sperm proteins and male infertility published in the English language in peer-reviewed journals were considered.
Keywords: Acrosome